2015
DOI: 10.1007/s11693-015-9178-6
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for robust oscillatory behavior

Abstract: Oscillatory responses are ubiquitous in regulatory networks of living organisms, a fact that has led to extensive efforts to study and replicate the circuits involved. However, to date, design principles that underlie the robustness of natural oscillators are not completely known. Here we study a three-component enzymatic network model in order to determine the topological requirements for robust oscillation. First, by simulating every possible topological arrangement and varying their parameter values, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…In agreement with previous work (Castillo-Hair et al, 2015; Goldbeter, 2002; Novak and Tyson, 2008), we found that certain core network topologies are essential for robust oscillations. However, we also found that local modifications on a node of the network have a significant impact on the global network robustness.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous work (Castillo-Hair et al, 2015; Goldbeter, 2002; Novak and Tyson, 2008), we found that certain core network topologies are essential for robust oscillations. However, we also found that local modifications on a node of the network have a significant impact on the global network robustness.…”
Section: Introductionsupporting
confidence: 93%
“…Despite the complexity and diversity of these oscillators, their central network architectures are highly conserved (Bell-Pedersen et al, 2005; Cross et al, 2011), suggesting that network topology is a key factor in determining the properties of biological oscillations. Studies have focused on the core topologies of oscillators, to understand the systems-level characteristics such as periodicity and robustness (Castillo-Hair et al, 2015; Lomnitz and Savageau, 2014; Nguyen, 2012; Novak and Tyson, 2008; Woods et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Philosophically, structure determines function, and the topology of networks is key to understanding their central properties [ 28 31 ]. The core topologies capturing the backbone of practically complex networks have been investigated for simple functions such as oscillations [ 32 ], adaptation [ 33 ] switch-like responses [ 34 ], dose-response alignment [ 35 ] and patterning in response to morphogen gradients [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of natural oscillatory systems makes it difficult to analyze their behaviors quantitatively. Uncovering functional properties of simple biological oscillators then becomes important for the understanding of various intracellular processes and the characterization of complex biological oscillators, and it is also helpful for the elucidation of design principles of biological oscillators [36,16,7]. In the spirit of synthetic biology, biological oscillators can be classified according to their topology [28,18,23,19], e.g., the oscillators of negative feedback loops, and those of interlocked positive feedback loop (PFL) and negative feedback loop (NFL), which are denoted by iPNFL for brevity.…”
mentioning
confidence: 99%